Experimental Tooth Movement into New Bone Area Regenerated by Use of Bone Marrow–Derived Mesenchymal Stem Cells. (July 2015) - Tanimoto, Kotaro; Sumi, Keisuke; Yoshioka, Motoko; Oki, Nanae; Tanne, Yuki; Awada, Tetsuya; Kato, Yukio; Sugiyama, Masaru; Tanne, Kazuo
Objective: The aim of this study was to examine experimental tooth movement into regenerated bone in alveolar cleft with mesenchymal stem cells and a granulated carbonated hydroxyapatite scaffold. Design: An artificial bone defect was created bilaterally in upper incisor regions of beagle dogs to simulate alveolar clefts in patients with cleft palate. The mesenchymal stem cells derived from the iliac bone marrow were cultured and transplanted with carbonated hydroxyapatite into the bone defect area. Carbonated hydroxyapatite alone was transplanted on the control side. Six months after the transplantation, multi-bracket appliances were attached to the lateral incisors and canines on both sides of the maxilla to exert an orthodontic force of 100 × g using an elastic chain. The distance between lateral incisor and canine was measured, and standardized x-ray images were taken every month. The tissue after tooth movement was evaluated by histological observation. Results: The experimental tooth movement, accompanied by resorption of regenerated bone and new bone formation, was achieved on the experimental and control sides. Although there was no difference in the amount of tooth movement obtained on the experimental and control sides during the 6-month experimental period, the rate of tooth movement varied on the control side; whereas, the rate was consistent on the experimental side. Root resorption of the tooth was observed on the control side in one dog. Conclusion: It is suggested that mesenchymal/carbonated hydroxyapatite transplantation therapy has great potential as a new treatment modality for bone regeneration in patients with cleft palate.